A Dissemination to Farmer Group Members for Optimizing Coffee Harvest Yields in Ngadirejo Village, Malang Regency - Arnanda Ajisaputra; Made Iska Aprilita Wardani; Nurtjahja Juniarsa; Mohammad Rofiudin; Pudji Lestari (Sah Publisher, 2026)
Abstract. The optimization of farmer group members in utilizing coffee harvests is an important strategy for improving agricultural productivity, product quality, and community welfare. However, coffee farmer groups in Ngadirejo Village, Jabung District, Malang Regency continue to face several challenges, including limited technological adoption, inadequate post-harvest management, weak marketing networks, and insufficient managerial capacity. This community service program aimed to strengthen the capacity of farmer group members through dissemination activities, mentoring, and knowledge transfer related to coffee cultivation, post-harvest processing, organizational management, and marketing strategies. The program was implemented using a participatory dissemination approach involving direct interaction, training sessions, discussions, and continuous assistance. Activities included environmental observation, problem identification, capacity-building programs, dissemination of management and production knowledge, and evaluation of program progress. The implementation focused on enhancing farmers’ knowledge, technical skills, collaboration, access to information, and awareness of sustainable agricultural practices. The results indicate that the dissemination activities contributed positively to the development of farmer group members. Participants demonstrated improvements in knowledge, creativity, managerial capability, and understanding of post-harvest coffee processing techniques. Communication and collaboration among members became more effective, while access to marketing opportunities and production-related information improved. The program also encouraged a gradual shift from traditional farming practices toward a more organized and market-oriented agribusiness approach. Furthermore, productivity and the quality of management practices showed continuous improvement throughout the implementation period. This community service initiative demonstrates that dissemination combined with mentoring and participatory engagement can effectively strengthen the capacity of coffee farmer groups. The program contributes to improving productivity, supporting sustainable coffee agribusiness development, and enhancing community welfare. Continued support through technological innovation, institutional strengthening, and structured evaluation systems is recommended to ensure long-term sustainability and broader impact.